Sarcophaga dux Thomson (Diptera: Sarcophagidae) recovered from wrapped body of an infant: its evidential value - Raja Muhammad Zuha Raja Kamal Bashah,; Muhammad Hilmi Baba, (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
The decomposed body of a male infant was found in an oil palm estate in Rengit, Batu Pahat, Johor wrapped with clothes. Entomological specimens recovered in this case were flesh fly larvae, Sarcophaga (Liosarcophaga) dux Thomson and Sarcophaga peregrina (Robineau-Desvoidy) (Diptera: Sarcophagidae). Minimum post mortem interval (PMImin) was approximately 48 hrs based on the largest specimen, i.e. S. dux. This species has been featured as forensically important species in Malaysia but scarcity of developmental data and bionomics in cadaver environment limit its utilization in forensic case. Issues pertaining its evidential value in this case and recommendations are described herein.